2018
DOI: 10.1002/lary.27330
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maxillofacial Prosthetics for the Surgically Treated Patient at National Cancer Institute–Designated Comprehensive Cancer Centers

Abstract: Objectives/Hypothesis The current role of maxillofacial prosthetic care for head and neck cancer patients is not well understood. Additionally, perceived barriers for service provision are unknown. The purpose of this study was to evaluate the current role of maxillofacial prosthetic care at National Cancer Institute (NCI)–designated comprehensive cancer centers and to identify perceived barriers to care. Study Design Multicenter, cross‐sectional survey of head and neck division leaders at NCI‐designated compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The results of the available studies clearly prove the effectiveness of the use of obturators in patients who have undergone maxillectomy [21,22]. The main disadvantage of this solution is severe pain associated with the initial period of use.…”
Section: Discussionmentioning
confidence: 87%
“…The results of the available studies clearly prove the effectiveness of the use of obturators in patients who have undergone maxillectomy [21,22]. The main disadvantage of this solution is severe pain associated with the initial period of use.…”
Section: Discussionmentioning
confidence: 87%
“…Maxillofacial prosthodontics provides prosthetic rehabilitation for functions such as speech, swallowing, mastication, and esthetics and is a well-recognized subspecialty of prosthodontics [ 1 , 2 , 3 ]. In 2018, Yanagi et al conducted a study at the Clinic for Maxillofacial Prosthetics, Tokyo Medical and Dental University, and found that the average age of patients had shown an increasing trend over the previous 35 years and that almost 80% of patients had developed tumors in Japan’s now super-aging society [ 4 ], and we feel that this could be even higher now.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillofacial prostheses are an important tool in providing continuous supportive care to patients with maxillofacial defects, including in terminal care [ 1 , 2 ]. In other words, many patients would have difficulty surviving in daily life without their maxillofacial prosthesis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most head and neck oncology services that want to promote this multiprofessional approach do not have the necessary in-house professionals to address the patients' broad scope of needs. Therefore, patients are often referred externally or directed to rehabilitation services remotely located (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%